2021
DOI: 10.4209/aaqr.2020.07.0463
|View full text |Cite
|
Sign up to set email alerts
|

How are the Two Most Polluted Metro-cities of India Combating Air Pollution? Way Forward after Lifting of COVID-19 Lockdown

Abstract: The national capital region of Delhi and Kolkata are the two metro cities in India worst affected by poor air quality. Multiple policies have been declared and implemented by the city authority in the recent past with the hope of improving the air quality of the cities and to attain the national ambient air quality standard. This study assesses that these present policies can help to reduce air pollution in these cities as much as 20% in the optimistic assessment, which may not be sufficient to attain the clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Several studies have been published on the impacts of COVID-19 on air pollution level in India (Jain and Sharma, 2020;Kumar, 2020;Kumari and Toshniwal, 2020;Majumdar, 2020;Mahato, et al, 2020;Sharma et al, 2020;Shehzad et al, 2020;Singh and Chauhan, 2020). However, most of the studies have reported measurements of metro cities and urban regions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Several studies have been published on the impacts of COVID-19 on air pollution level in India (Jain and Sharma, 2020;Kumar, 2020;Kumari and Toshniwal, 2020;Majumdar, 2020;Mahato, et al, 2020;Sharma et al, 2020;Shehzad et al, 2020;Singh and Chauhan, 2020). However, most of the studies have reported measurements of metro cities and urban regions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Air quality was declining in many cities [17][18][19] and its impacts are more pronounced around the globe [20][21][22] causing economic loss and diseases [23][24][25]. Earlier researchers reported decreasing trend of air pollutants due to lockdown period, [26][27][28][29][30][31][32][33] reduced anthropogenic emissions [34], meteorological impacts on air concentration [35][36]. Many researchers have studied AQI in Chennai city [32,[37][38] but they have not done micro level analysis.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Moreover, the median PM2.5 concentrations vary depending on the geographical location and the time of year. Some cities in Asia struggle with higher medial PM2.5 concentrations than those located in other parts of the globe [7]. The PM2.5 concentrations in urban areas tend to be higher in winter than in other seasons of the year [8].…”
Section: Introductionmentioning
confidence: 97%